International evidence on the influence of kindergarten on students’ later competences. - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (My University, 2023)
Parents have the option to enrol their children in kindergarten education (from 0 to 3 years) in many countries, although not all parents decide to do it, so their children are enrolled when they are between 3 to 5, or even when they reach the age of 6 and have to attend compulsory. The present research study analyses the influence of students’ attendance to kindergarten on their 4th grade reading scores. In order to carry out this research, data from PIRLS 2011 and 2016 for 34 countries and an instrumental variable approach – to go beyond simple correlation – have been employed. Our results show that kindergarten attendance has a positive influence on students’ reading scores in 18 of the countries under analysis, whereas it presents a null influence in 16 countries.
Keywords: Enseñanza preescolar; Kindergarten; Instrumental variables; Fourth grade; Reading